2021
DOI: 10.1088/1361-665x/ac277e
|View full text |Cite
|
Sign up to set email alerts
|

A new design of small-sized magnetorheological brakes based on the mixed mode operation for high torque efficiency

Abstract: A small-sized brake generating the torque less than 0.5 Nm is very attractive to achieve desired dynamic motions in many different fields such as medical haptic and auto door closure. In this work, a controllable compact-sized brake utilizing a magnetorheological fluid (MRF) is proposed and its effectiveness is validated through simulation and experiment. Unlike conventional shear mode magnetorheological brake (MRB), a mixed mode MRB (M-MRB) featuring both the flow and shear mode operations is designed to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The MRF brake or clutch is normally designed following the multi-disc model presented in [61][62][63]. MRF brake has many modifications, including the conventional model with a single coil in [42,64,65], and a floweredge section model [66] for increasing the contacted area. It can be defined as a multi-coil, as shown in [42], for improving the magnetic field and optimizing the operation coil.…”
Section: Mrfmentioning
confidence: 99%
“…The MRF brake or clutch is normally designed following the multi-disc model presented in [61][62][63]. MRF brake has many modifications, including the conventional model with a single coil in [42,64,65], and a floweredge section model [66] for increasing the contacted area. It can be defined as a multi-coil, as shown in [42], for improving the magnetic field and optimizing the operation coil.…”
Section: Mrfmentioning
confidence: 99%
“…Magnetorheological grease materials have advantages such as good resistance to settling, leakage prevention, strong magnetorheological effects, and ease of preparation, as their viscosity is based on a combination of liquid magnetorheological fluid and solid magnetorheological elastomers. Therefore, they have found wide application in devices such as dampers [ 5 ], buffers [ 6 ], clutches [ 7 ], and brakes [ 8 ], and have promising prospects for further use. However, magnetorheological greases still have some drawbacks, such as high zero-field viscosity and susceptibility to shear-thinning.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetorheological clutch was allowed to operate as the main clutch. Song et al (2021) designed a small magnetorheological brake based on a hybrid mode of shear and flow, which can provide higher torque using a relatively small amount of the magnetorheological fluid. Tian et al (2022) studied the time response characteristics of MRTDs and found that changing the parameters of the excitation coil and the number of taps can effectively shorten the current response time.…”
Section: Introductionmentioning
confidence: 99%